Analisis Hukum terhadap Akuntabilitas Komisi Pemilihan Umum dalam Penetapan Hasil Pemilu - Luh Putu Devina Praditha Putri; Ni Ketut Sari Adnyani; Ni Putu Ega Parwati; I Nyoman Budiada (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
This study aims to analyze the accountability of the General Election Commission (Komisi Pemilihan Umum/KPU) in determining election results from a legal perspective in Indonesia. The research focuses on examining the legal principles, regulatory framework, and institutional responsibilities that govern the KPU in carrying out its authority to determine election results. This study employs a normative legal research method using statutory (statute approach) and conceptual (conceptual approach) approaches. The statutory approach examines relevant laws and regulations governing elections and the KPU, while the conceptual approach analyzes legal doctrines and theories related to accountability, transparency, and democratic governance. The findings indicate that the accountability of the KPU must be realized through compliance with applicable laws and regulations, transparency, professionalism, independence, and integrity in every stage of determining election results. The implementation of these principles plays an essential role in ensuring legal certainty, protecting electoral justice, strengthening public trust, and promoting democratic, fair, and credible elections. Therefore, strengthening the accountability of the KPU is essential to maintaining the legitimacy, integrity, and public acceptance of election results while supporting the sustainability of Indonesia's democratic system.